2011
DOI: 10.1177/1545109710385121
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Low-Dose Indinavir/Ritonavir (IDV/r)- versus Atazanavir/Ritonavir (ATV/r)-Based Generic Antiretroviral Therapy in NNRTI-Experienced HIV-1-Infected Patients in India

Abstract: Background: Currently, data on the effectiveness of second-line antiretroviral regimens using indinavir/ritonavir (IDV/r) and atazanavir/ritonavir (ATV/r) along with 2 nucleoside reverse transcriptase inhibitor (NRTI) in resource-poor settings is limited. Methods: Observational follow-up study on 441 patients who experienced treatment failure to first-line nonnucleoside reverse transcriptase inhibitor (NNRTI)-based treatment. Multivariate Cox Proportional Hazards Model was used to assess comparative effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…We obtained data from 12 papers pertaining to eight studies (figure 1). [9][10][11][12][13][14][30][31][32][33][34][35] These studies included 4778 patients from five continents, and most studies were from resource-limited settings (table). The appendix provides a list of included and excluded studies at full-text review (pp 5-15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained data from 12 papers pertaining to eight studies (figure 1). [9][10][11][12][13][14][30][31][32][33][34][35] These studies included 4778 patients from five continents, and most studies were from resource-limited settings (table). The appendix provides a list of included and excluded studies at full-text review (pp 5-15).…”
Section: Resultsmentioning
confidence: 99%
“…We did fixed-effects network meta-analysis of the mean differences in change in CD4 cell count from baseline to 24 and 48 weeks, using results from six studies (five randomised controlled trials and two cohort studies) 10,11,14,31,[33][34][35] involving 4304 participants. Findings showed that increases in mean CD4 count were significantly higher with ritonavir-boosted lopinavir plus raltegravir than with ritonavir-boosted lopinavir plus two NRTIs at 48 weeks (mean difference 23•02 cells per µL, 95% CrI 10•09-36•17; figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The increase of multidrug-resistant (MDR) bacteria induced a renewed interest in old antibiotics, such as fosfomycin (6) . Because of its broad-spectrum activity,sustained urinary concentrationsand its safety profile.…”
Section: Introductionmentioning
confidence: 99%